Совершенствование учета затрат на инновационную деятельность организации - Nataliya Stepanovna Plaskova; Tat’yana Aleksandrovna Polyanskaya; Aleksandr Sergeevich Samusenko (Учёт. Анализ. Аудит, 2019)
Introduction, Purpose. The Activation of the innovative activity in an organization helps to increase the competitive strengths and advantages as well as to strengthen its market positions in the modern economic conditions. The improvement of the cost accounting of the innovative activity should contribute to the optimization of current and capital costs on different stages of an innovative product creation and provide different users with the objective and timely information about the innovative activity in order for them to take managerial decisions. Methods. The article provides specialists’ overviews about the definitions of innovative activity and current and capital costs formed in process of innovative activity as the subjects of accounting. The organization of accounting of economic operations connected with innovative activity depends on stages of life cycle of innovations created by the company. The article demonstrates the stages of consecutive development of an innovative product, starting with the creation of the scientific idea, and ending up with the commercialization of the innovative product. It formed the basis of the proposed scheme of correspondence of accounts. Results. The article demonstrates the methods for organization of accounting of different types of innovative costs formed during each stage of innovative activity, which allows to form accounting information with a reasonable degree of analyticity. Based on the recommendations by Russian and international documents which regulate the accounting of innovative activity using the complementary approach, the article suggests keeping detailed accounting of current and capital innovative costs by types of innovations, stages of innovative process, projects incurred by internal activities or external organizations. The article demonstrates the systematic correspondence of accounts of various economic operations in the process of innovative project realization, starting with primary costs and accounting of resources, and ending up with the formation of financial results. Discussion. Methodological and practical approaches about the organization of the accounting of innovative activity proposed in the article should contribute to the improvement of the accounting process and enhance to the quality of information support of managerial decisions in innovative companies as well as the growth of their efficiency and competitiveness.